(untitled) (Castilla. Estudios de Literatura, 2022)
This article points out the social determination of the cinematic image as a direct cause of the analogy between the different arts during the period of the First Avant-Garde. In particular, it delves into the expressive reciprocity of Cinema and New Poetry confirmed by numerous theoretical and practical contributions, such as those of the ultraist poet Guillermo de Torre or those of the surrealist filmmaker Luis Buñuel. Likewise, the convenience of applying the concepts of cinema-eye (1919) and cinema-truth (1922), by the Russian director Dziga Vértov, and that of mental cinema (1989), by the Italian writer Italo Calvino to explain the aesthetic foundations and poetics of this osmosis, which the final comparative reading of the creationist poem “Lluvia” by the Spanish Gerardo Diego and the film of the same name by the Dutch Joris Ivens shows.